Organizational Stress Among West Visayas State University - Lambunao Campus Personnel: Basis for Stress Management Program - Dimo, Sherina D; Bunda, Rhea A (President University, 2024)
This study aimed to determine the level of organizational stress among personnel at West Visayas State University - Lambunao Campus. A total of 61 respondents were conveniently selected with their consent to participate in the study. An adapted and modified survey questionnaire was utilized to assess the participants' organizational stress levels in four key areas: task demand, physical demand, role demand, and interpersonal demand. Additionally,the study examined differences in stress levels when grouped according to personal-related factors. The research employed a descriptive-survey design, utilizing statistical tools such as frequency, mean, Kruskal-Wallis H Test, and Mann-Whitney U Test for data analysis.The findings revealed that the personnel experienced a moderately high level of organizational stress in task demands, physical demands, and role demands, while a low level of stress was observed in interpersonal demands when analyzed by personal-related factors. Furthermore, the study identified that marital status, monthly income, length of service, position for staff, and additional assignments for faculty were associated with higher levels of stress in terms of task and physical demands. This suggests that faculty and staff with heavier workloads or increased responsibilities are more likely to experience higher stress levels compared to those with fewer responsibilities. The results also indicate that higher levels of demand, a sub-component of stress, can lead to decreased work performance.